Culture and communication : signs in flux : an anthology of major and lesser-known works - Lotman, I͡U. M. (I͡Uriĭ Mikhaĭlovich), 1922-1993 (Cultural syllabus., 2020)
"Yuri Lotman (1922-1993) was one of the most prominent and influential scholars of the twentieth century working in the Soviet Union. A co-founder of the Tartu-Moscow school of semiotics, he applied his mind to a wide array of disciplines, from aesthetics to literary and cultural history, narrative theory to intellectual history, cinema to mythology. This collection provides a stand-alone primer to his intellectual legacy in both semiotics and cultural history. It includes new translations of some of his major pieces as well as works that have never been published in English. The collection brings Lotman into the orbit of contemporary concerns such as gender, memory, performance, world literature, and urban life. It is aimed at students from various disciplines and is augmented by an introduction and notes that elucidate the relevant contexts"--